Measurement of faba bean grain yield and aboveground biomass at maturity: v1. Standard Operating Procedure 016 - Devkota, Mina (CGIAR System Organization, 2025)
SOP ID: 016 Version: 1 Crop: Faba bean (Vicia faba) Relevant KPIs: Productivity — yield; Resource use efficiency — nutrient use efficiency R&D stage (example of activities): • Discovery stage (yield decomposition) • Proof-of-concept stage (testing of improved agronomic practices in on-station and/or on-farm trials) • Pilot stage (on-farm participatory trials, randomized control trial) • Scaling stage (panel studies, ex-post impact assessment)